2017
DOI: 10.1021/acsomega.7b00608
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Putative B-Cell Zika Virus NS1 Epitopes Provides Molecular Basis for Anti-NS1 Antibody Discrimination between Zika and Dengue Viruses

Abstract: B-cell epitope sequences from Zika virus (ZIKV) NS1 protein have been identified using epitope prediction tools. Mapping these sequences onto the NS1 surface reveals two major conformational epitopes and a single linear one. Despite an overall average sequence identity of ca. 55% between the NS1 from ZIKV and the four dengue virus (DENV) serotypes, epitope sequences were found to be highly conserved. Nevertheless, nonconserved epitope-flanking residues are responsible for a dramatically divergent electrostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 60 publications
4
38
0
1
Order By: Relevance
“…A network analysis can increase insight into the biological organization and the driving forces behind those mutations. However, in the context of infantile microcephaly and the other complications associated with Zika infection, the results reported here, in agreement with the findings of Freire et al [15], suggest that the immunogenicity, toxicity and protective effectiveness of these three peptides should expeditiously be tested experimentally for potential clinical usefulness.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…A network analysis can increase insight into the biological organization and the driving forces behind those mutations. However, in the context of infantile microcephaly and the other complications associated with Zika infection, the results reported here, in agreement with the findings of Freire et al [15], suggest that the immunogenicity, toxicity and protective effectiveness of these three peptides should expeditiously be tested experimentally for potential clinical usefulness.…”
Section: Resultssupporting
confidence: 91%
“…The data and analysis presented here support and expand the data and analysis presented by Freire et al [15] and therefore suggest that the observed Shannon entropy may be associated with immunological activity. Unfortunately, not all immunological activity is favorable to the infected host.…”
Section: Journal Of Medical Microbiology and Diagnosissupporting
confidence: 89%
See 2 more Smart Citations
“…34 Nonetheless, it is imperative to consider the possible implications of virusinfection enhancement. 31,39,40 While various reports have shown the specificity of the NS1 antigen to differentiate between ZIKV and DENV, 11,20,21,41,42 the majority of the common flavivirus peptides identified in this study are on the NS1 protein, possibly because of the conserved regions of NS1 among the flaviviruses. 35,36 Peptides identified from B-cell epitope mapping have been reported on flavivirus E, prM, NS1 and NS3 antigens from antibodies of patients and animal models.…”
Section: Discussionmentioning
confidence: 68%